FACTORS OF AUDITOR'S READINESS IN IMPLEMENTING IFRS IN INDONESIA - Nanang Shonhadji (Universitas Hayam Wuruk Perbanas, 2012)
Accounting standards in Indonesia has harmonically been ready to implement internationalaccounting standards or International Financial Reporting Standards (IFRS). The purpose ofthis study was to find out the effect of readiness on the competence, expertise and experienceof auditors on the implementation The International Financial Reporting Standard (IFRS) inIndonesia in 2012. This study has shown that auditor’s competence and experience had significantinfluence while they will implement of IFRS in Indonesia in 2012 but auditor’s expertisedidn’t have significantly influence towards the implementation of IFRS. Questionnaireswere distributed to selected auditors who work in several Public accountant offices. The implicationis that auditors should have good knowledge to make sufficient adjustments whilethey want to convert the SAK (General Accounting Standard in Indonesia) to IFRS. They alsohave to understand the technique of audit in international environment by formal and informaleducation. Junior auditors need to improve audit skills and self confidence in orderreadiness to implement IFRS.